The Use of Vlog in Improving Students’ Oral Language Production: A Case Study - Saputro, Teguh Hadi; Tafsirudin, Ibnu Choirin; Farah, Rafika Rabba (Universitas Islam Negeri Raden Intan Lampung, 2020)
The analysis of using a video blog (Vlog) in language learning has been widely done. However, most of the studies only focus on investigating the students’ perception of Vlog. This study attempted to analyze the use of Vlog in improving students’ oral language production. In addition, the students’ perception after applying Vlog in language learning was also investigated. The complexity, accuracy and fluency (CAF) were the aspects analyzed from students’ performance. Further, a mixed-method was applied in this study. This study involved six participants (3 male and 3 female) who were the students of the English Language Education Department of a private university in Malang, Indonesia. A speaking test which was in the forms of vlogs and semi-structured interviews were used as the instruments for the data collection. The quantitative data from the test were calculated by using formulas of CAF and further analyzed by the descriptive statistics, while the qualitative data from the interview were analyzed to explore the benefits and challenges of learning with vlogs. The findings showed the increasing mean of the students’ accuracy while their fluency and complexity decreased. There were several factors that might impact the findings. Those were; planning time, pressures, restrictions in terms of time, and task repetition. The benefits and challenges of learning with Vlogs were discussed in this paper.